PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN RETURN ON ASSET SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Sitorus, Andreas (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The purpose of this study was to examine the effect of good corporate governance on firm value mediated by return on assets in insurance companies listed on the Indonesia stock exchange in the 2017-2021 period. The sample collection technique using purposive sampling obtained a total of 14 companies and in this study researchers used descriptive and associative statistics. The data analysis technique used in this study is multiple regression analysis and expanded with path analysis, sobel test, classical assumption test, and coefficient of determination. The results of this study indicate that the audit committee has a positive effect on Tobins'Q, institutional ownership has a negative effect on Tobins'Q. while the independent board of commissioners, return on assets has no effect on Tobins'Q. Return on assets cannot mediate against institutional ownership of Tobins'Q, Return on assets cannot mediate against independent commissioners on Tobins'Q, Return on assets cannot mediate against the audit committee on Tobins'Q Keywords: institutional ownership, independent board of commissioners, audit committee, return on assets, tobins'q